Latin American Christology: A God Who Liberates - Bolaños, Amanda Rachel (Religions, 2024)
This paper will investigate the dynamic nature of Latin American Christology, a Christology that cannot be separated from the tenets of liberation theology. I will first offer an overview of the development of Latin American Christology and liberation theology, along with its unique features; then, I will analyze some major representatives of Latin American Christology, specifically Jon Sobrino and St. Óscar Romero (through the research of Edgardo Colón-Emeric). Lastly, I will conclude with the relevance of Latin American Christology within the greater landscape of Christian theology today. The theologians considered in this paper are primarily Catholic theologians, with the exception of Edgardo Colón-Emeric, a Methodist pastor, who has become a global voice of authority on the life, thought, and vision of the martyred St. Óscar Romero. Latin American Christology, as will be argued in this paper, cannot be understood separately from the space, culture, and identity of Latin America—the land and the context. This measures to a pivotal pedagogical claim of Latin American Christology as a global teaching pillar for all Christologies and theologies, Catholic or Protestant, within Latin America or outside Latin America.